Analisis Lingkungan Kota Di Kecamatan Maritengngae, Sidenreng Rappang - Haq, Izharul; Baharuddin, Hasniar; Kamaruddin, Nurhayati (JARI: Journal of Architecture, Research and Innovation, 2024)
This study aims to analyze the urban environmental conditions in Maritengngae District, Sidenreng Rappang Regency, focusing on land use, green open spaces, air quality, waste management, and supporting infrastructure. This research uses a qualitative approach with data collection techniques through in-depth interviews, field observations, and documentation. The results show that land use in Maritengngae District has undergone significant conversion, with a reduction in green open spaces due to the transformation of land into residential and commercial areas. This has led to a decline in environmental quality, including air quality, which is indicated to have deteriorated due to the increased number of motor vehicles and industrial activities. Additionally, waste management in the area faces challenges, with low community awareness in waste sorting and limited facilities for waste management based on the 3R (reduce, reuse, recycle) principle. However, there are positive efforts from the local government, such as the development of city parks and eco-friendly drainage systems, which are expected to improve environmental quality. This study suggests that government policies should be more integrated with community participation and adequate funding to create a sustainable urban environment in Maritengngae District.